PEMBERIAN REBUSAN SARI KUNYIT (CURCUMA LONGA LINN) PADA REMAJA PUTRI DENGAN FLOUR ALBUS PATOLOGIS PASCA MENSTRUASI - Pramulya, Asmaurina; Renasari Presty, Marsela; Audina, Marchella; Susanna, Susanna (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Vaginal discharge in women in Indonesia reaches 75%, where some women in Indonesia have experienced vaginal discharge, either once or more than once. Every year, cases of vaginal discharge in Indonesia continue to increase. In women aged 15–24 years, 31.8% experience vaginal discharge. Adolescent girls have a higher risk of experiencing vaginal discharge, cases of vaginal discharge that occur in women as much as 50%. To overcome vaginal discharge, there is a non-pharmacological method, namely giving turmeric drinks while maintaining personal hygiene genitalia is effective in reducing vaginal discharge. Objective: This study aims to determine the effect of giving boiled turmeric juice (Curcuma Longa Linn) to adolescent girls in overcoming pathological post-menstrual flour albus. Methods: This type of research is quantitative using a quasi-experimental method with a One Group Pre test–Post test Design research design. The population in this study were 228 adolescent girls at SMK Negeri 5 Pontianak. The number of samples was 34 adolescent girls with a purposive sampling technique. The instruments used were an observation sheet and SOP (Standard Operating Procedure) for making boiled turmeric juice. Data collection was conducted during the intervention for 7 consecutive days (pretest and posttest). Results: The results of the univariate analysis showed that before the intervention, 34 (100%) respondents had pathological flour albus. After the intervention, 23 (67.64%) respondents experienced physiological flour albus. Bivariate analysis using the Wilcoxon Signed Rank Test obtained a Z-score of -5.124 with a significance level (Asymp. Sig. 2-tailed) of 0.000. This indicates a statistically significant difference before and after the intervention. Conclusion: The effect of giving boiled turmeric juice (Curcuma Longa Linn) to adolescent girls in overcoming pathological post-menstrual flour albus.